Giving voices to the voiceless gender-based violence in the occupied Palestinian territories - Abu-Duhou, Jamileh (American University in Cairo Press, 2011)
Gender-based violence affects women throughout their lives and occurs in different abusive forms, including physical, psychological, sexual, and economic abuse. Gender-based violence has a diverse impact on women and may result in homicides, suicides, and many adverse health problems. It occurs as a result of gender roles and cultural norms, which influence the expression of violence within intimate relationships. In Palestinian society, such violence is about exertion of control and a sanctioned way of life - a way of life that is legitimized by religion and culture. The level of violence experienced is heightened by the on-going violent conflict in Palestine, which adds to the level of violence against women due to increased feelings of despair, loss of control, and emasculation among Palestinian men. Regardless of their age, religion, or social economic status, Palestinian women are rarely heard. The culture requires that they are not to be seen nor heard outside the confines of the home. This book, a collection of voices of Palestinian women victimized both by the ongoing violent conflict and at the hands of their husbands, redresses this imbalance.